ØªÙ‚ÙˆÙŠÙ… Ù…Ù‡Ø§Ø±Ø© Ø§Ù„ÙƒÙ„Ø§Ù… ÙÙŠ ØªØ¹Ù„ÙŠÙ… Ø§Ù„Ù„ØºØ© Ø§Ù„Ø¹Ø±Ø¨ÙŠØ© Ù„Ø·Ø§Ù„Ø¨Ø§Øª Ø§Ù„ÙØµÙ„ Ø§Ù„Ø«Ø§Ù…Ù† ÙÙŠ Ø§Ù„Ù…Ø¯Ø±Ø³Ø© Ø§Ù„Ù…Ù†ÙˆØ±Ø© Ø§Ù„Ù…ØªÙˆØ³Ø·Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙƒÙ…Ø¨Ù„Ø§Ùƒ Ø¬ÙˆÙ…Ø¨Ø§Ù†Ø¬ - Kurrotul Ainiah; Mu'at (Program Studi Pendidikan Bahasa Arab, 2020)
In this article, it is explained about the various kinds of evaluations on learning maharah al-kalam in Arabic at Madrasah Tsanawiyah Putri Al-Munawaroh grade 8, because evaluation is an element that is very and cannot be separated from the components of a curriculum which consists of learning objectives, materials, methods & learning media, the last is a component. In this case, the evaluation of maharah kalam includes conversation, hiwar and others. And the teacher must see the speaking activity, as well as the various exercises obtained as a whole, that the role of students is notended only after they were able to master the dialogue and memorize it, but also must be able to implement in real life situations. This article uses a qualitative research approach, a case study model in the grade 8 female Islamic school at Tsanawiyah Al-Munawaroh Putri. The data collection instruments used observation, interviews and documentation. The results of this study are that there are various steps used by the teacher to evaluate the students' abilities in mastering maharah al-kalam, namely: 1) speaking ability by describing a picture, 2) practicing conversation, 3) practicing free speaking, 4) speaking based on experience personally, 5) practice talking with other friends.